2017
DOI: 10.4195/nse2017.02.0004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Education at the Special School: Opinions of Special Education Teachers

Abstract: Core Ideas Environmental education in special education is feasible. Environmental education requires further training of educators. Environmental education is beneficial to children with disabilities. This investigation, conducted in Greece, inquired 80 special education teachers—via a structured questionnaire—their opinions on whether they feel ready to teach environmental education (EE) to pupils with disabilities, whether instruction of EE is possible in special or in regular education classes, and wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
3
Order By: Relevance
“…transportation, excessive consumption, land change processes) with the increase of greenhouse gases emission (Ghilardi-Lopes et al, 2013). In addition, many studies have shown that environmental education is not a priority in schools and in continuing education programs for teachers (Lappa, Kyparissos, & Paraskevopoulos, 2017). Finally, if we consider "marine environmental education" in Brazil the initiatives are rare (Berchez et al, 2007), despite their vast importance in the development of a conscience focused on the conservation of marine ecosystems.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…transportation, excessive consumption, land change processes) with the increase of greenhouse gases emission (Ghilardi-Lopes et al, 2013). In addition, many studies have shown that environmental education is not a priority in schools and in continuing education programs for teachers (Lappa, Kyparissos, & Paraskevopoulos, 2017). Finally, if we consider "marine environmental education" in Brazil the initiatives are rare (Berchez et al, 2007), despite their vast importance in the development of a conscience focused on the conservation of marine ecosystems.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Οι ερευνητές επέλεξαν τη 5/βάθμη κλίμακα Likert, για να δημιουργήσουν το δικό τους ερευνητικό εργαλείο. Επίσης, βασίστηκαν στη φιλοσοφία των δηλώσεων που υπάρχουν σε προηγούμενη έρευνα των Lappa et al (2017). Οι συγκεκριμένες δηλώσεις χρησιμοποιήθηκαν, για να εξεταστούν σε ποσοτικό επίπεδο οι απόψεις των εκπαιδευτικών διαφόρων ειδικοτήτων για τη συμβολή της Π.Ε.…”
Section: εργαλείο συλλογής δεδομένων-διαδικασίαunclassified
“…σε παιδιά με αναπηρία. Η συγκεκριμένη διαπίστωση συμφωνεί εν μέρει με την έρευνα των Lappa et al (2017), στην οποία οι εκπαιδευτικοί δεν νιώθουν προετοιμασμένοι και έτοιμοι να διδάξουν την Π.Ε. σε μαθητές με αναπηρίες, καθώς πιστεύουν πως δεν διαθέτουν την κατάλληλη κατάρτιση ούτε επαρκείς γνώσεις σχετικά με τον τρόπο διδασκαλίας της Π.Ε.…”
Section: συζήτησηunclassified
See 1 more Smart Citation
“…Moreover, the fact that there is no of icial policy for E.E. in special schools in the curriculums, makes its application even more dif icult Lappa et al (2017).…”
Section: Introductionmentioning
confidence: 99%